2017
DOI: 10.1039/c7sm01504f
|View full text |Cite
|
Sign up to set email alerts
|

Active Brownian equation of state: metastability and phase coexistence

Abstract: As a result of the competition between self-propulsion and excluded volume interactions, purely repulsive self-propelled spherical particles undergo a motility-induced phase separation (MIPS). We carry out a systematic computational study, considering several interaction potentials, systems confined by hard walls or with periodic boundary conditions, and different initial conditions. This approach allows us to identify that, despite its non-equilibrium nature, the equations of state of Active Brownian Particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(108 citation statements)
references
References 44 publications
7
100
0
Order By: Relevance
“…As the phase diagram confirms [17], there opens a small window where the system is not yet crystallized and not yet phase-separated. We discuss two packing fractions for this case, η = 0.6 and η = 0.7.…”
Section: Active Hard Disksmentioning
confidence: 60%
See 2 more Smart Citations
“…As the phase diagram confirms [17], there opens a small window where the system is not yet crystallized and not yet phase-separated. We discuss two packing fractions for this case, η = 0.6 and η = 0.7.…”
Section: Active Hard Disksmentioning
confidence: 60%
“…Note however that for strong self-propulsion and/or fast reorientational diffusion, significantly smaller time steps may be required. The extension to active particles has been used to study glassy dynamics of dense AHS systems [18], and more recently also MIPS [17].…”
Section: Methods and Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the mean-field behavior of active Brownian particles can be mapped onto an effective free energy [31,51] and thus follows the same scenario as passive liquid-gas coexistence, although the non-equilibrium nature manifests itself in phenomena like a negative interfacial tension [52] and "bubbly" phase separation [53]. Neverthe- less, the generic relation with passive liquid-gas coexistence has been corroborated by detailed numerical investigations of the phase behavior [27,52,[54][55][56]. The resulting phase diagram in the v 0 -ρ plane is sketched in Fig.…”
Section: Coexistence Without a Critical Pointmentioning
confidence: 87%
“…Second, our general theory disregards higher order gradient terms in equation (1). This probably explains why the hydrodynamic description works best fairly close to the critical point, where interfaces are smoothest and the gradient expansion, equation (38), most accurate. The quantitative limitations of our gradient expansion highlights that gradient terms directly influence the coexisting densities through equation (11), unlike the equilibrium case.…”
Section: Comparison Between Theory and Numericsmentioning
confidence: 95%